تبسيط صياغة التحليل الإنشائي للجيزان بطريقة الانتقالات - أكرم صقور (Tishreen University, 2019)
يتضمن البحث صياغة التحليل الإنشائي للجيزان المستمرة بطريقة الانتقالات في علاقات مبسطة يمكن تعميم استخدامها على جميع أنماط الجيزان، التي تتعرض عقدها إلى الدوران بتأثير الحمولات الخارجية. إذ تسمح هذه العلاقات بإجراء التحليل اللازم وحساب الدورانات والعزوم النهائية في عقد الجائز دون الحاجة إلى: 1- تكرار رسم مخططات العزوم لفتحات الجائز الناتجة عن تدوير الوثاقات الوهمية المقيدة لدرجات الحرية في هذه   العقد والمتمثلة بالدوران. 2- تكرار إجراء التوازن المنفرد على كل عقدة للحصول على المعادلات اللازمة لإيجاد قيم المجاهيل في هذه العقد.   The present Paper shows a formulation of the structural analysis of Continuous Beams, by using of simplified equations of Displacements Method, that can be used for all types of beams with rotated nodes resulted from external loads. The advantage of these equations is analyzing the beam and computing its nodes rotations and final moments, without need of the following: • Repeating the drawing of moment diagrams resulted from the supposed fastened supports that restrict the nodes freedom degree (rotation). • Repeating of the single balance of each node to get the necessary equations for computing these nodes unknowns.